2001
DOI: 10.1146/annurev.micro.55.1.453
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Parasite-Vector and Vector-Host Interactions in Leishmaniasis

Abstract: Leishmania-sand fly interactions are reviewed in the context of the potential barriers to the complete development of the parasite that exist within the midgut environment of phlebotomine flies and the molecular adaptations that the parasite has evolved that permit the development of transmissible infections to proceed. Cell surface and secreted phosphoglycans protect the parasite from the proteolytic activities of the blood-fed midgut, mediate attachment to the gut wall in order to maintain infection during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
277
0
36

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(316 citation statements)
references
References 115 publications
3
277
0
36
Order By: Relevance
“…As demais amostras positivas apresentaram ambas as formas nas regiões do piloro, íleo e papila retal, ou seja, porções do trato digestivo posterior. Os resultados obtidos neste estudo são discordantes de outros que relataram a presença de formas procíclicas na porção anterior do estômago e nectomonadas no estômago, cárdia e válvula do esôfago 5,6 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…As demais amostras positivas apresentaram ambas as formas nas regiões do piloro, íleo e papila retal, ou seja, porções do trato digestivo posterior. Os resultados obtidos neste estudo são discordantes de outros que relataram a presença de formas procíclicas na porção anterior do estômago e nectomonadas no estômago, cárdia e válvula do esôfago 5,6 .…”
Section: Resultsunclassified
“…Realizou-se dissecação de, em média, dez fêmeas por captura. O trato digestivo e a cabeça foram retirados e observados para verificar a presença de formas evolutivas de Leishmania, segundo nomenclatura utilizada por Walters et al 5 e Sacks & Kamhawi 6 . A taxonomia dos insetos foi realizada de acordo com seus caracteres morfológicos 7 .…”
Section: Methodsunclassified
“…1B), consistent with similar studies with promastigotes of L. major (data not shown). Maintenance of stationary phase viability is critical, since promastigotes differentiate in stationary phase to the infective metacyclic form of the parasite [3,31]. In contrast, the viability of LdB amastigotes decreased more substantially in stationary phase, dropping to less than 90% after 2 days (Fig.…”
Section: Viability In Liquid Media and Plating On Semisolid Mediamentioning
confidence: 95%
“…P. sergenti and P. papatasi are almost certainly the primary vectors of Leishmania tropica (Wright) and Leishmania major Yakimoff & Schokhor, respectively (Al-Azawi and Abul-Hab 1977, KillickKendrick et al 1985, Al-Zahrani et al 1988, KillickKendrick 1990. Sukkar (1978) suggested that P. papatasi was also the primary vector of visceral leishmaniasis [Leishmania donovani (Laveran & Mesnil) and/or Leishmania infantum Nicolle]; however, P. papatasi is a restricted vector and is incapable of transmitting any species of Leishmania other than L. major (Sacks and Kamhawi 2001). Killick-Kendrick (1990) reported that data from Li-Ren et al (1986) indicated that P. alexandri should be considered a potential vector of visceral leishmaniasis in Iraq.…”
mentioning
confidence: 99%